(untitled) (UNIZIK Journal of Marketing, 2025)
Effective inventory management plays a vital role in ensuring operational efficiency and quality service delivery in manufacturing. This study explores the relationship between Activity-Based Classification (ABC) inventory control and service delivery performance in selected manufacturing companies in South West Nigeria. The research was guided by two research questions, focusing on how the periodic inventory system influences responsive customer support in South West, Nigeria, and how Just-in-Time (JIT) inventory management impacts on-time delivery in South West Nigeria. Anchored on Systems Theory, the study employed a quantitative research design. Data were obtained from 300 purposively selected respondents across inventory, logistics, and customer service departments in the targeted firms. A structured questionnaire served as the primary instrument for data collection. To ensure the validity, the instrument was reviewed by domain experts. A pilot study involving 30 non-sample respondents was conducted to test reliability. The instrument yielded a Cronbach’s Alpha of 0.83, confirming strong internal consistency. Data were analyzed using SPSS version 26, applying inferential statistics of Pearson correlation. Results reveal a significant positive relationship between the periodic inventory system and responsive customer support (r = 0.856, p = 0.032), suggesting that well-managed periodic reviews contribute to improved customer responsiveness. Additionally, a very strong and statistically significant correlation was found between JIT inventory management and on-time delivery (r = 0.976, p = 0.020), highlighting the efficiency of JIT practices in meeting delivery timelines. The findings underscore the need for manufacturing firms to strategically align inventory management practices with customer service objectives to boost competitiveness and service quality. The study recommends the adoption of technology-enhanced periodic inventory systems and the integration of JIT practices tailored to each firm’s operational structure and market demands. These measures are essential for improving responsiveness, reducing inefficiencies, and achieving sustainable service excellence.